2011
DOI: 10.1103/physreve.83.046127
|View full text |Cite
|
Sign up to set email alerts
|

Vertex centralities in input-output networks reveal the structure of modern economies

Abstract: Input-output tables describe the flows of goods and services between the sectors of an economy. These tables can be interpreted as weighted directed networks. At the usual level of aggregation, they contain nodes with strong self-loops and are almost completely connected. We derive two measures of node centrality that are well suited for such networks. Both are based on random walks and have interpretations as the propagation of supply shocks through the economy. Random walk centrality reveals the vertices mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 33 publications
(33 reference statements)
3
118
0
3
Order By: Relevance
“…An early attempt taking input-output as the starting point can be found in Olsen (1992). More recently McNerney (2009) studies the network properties of input-output models, while Blöchl et al (2011) use centrality measures and clustering techniques to uncover salient structural features of economies based on an interpretation of input-output tables as weighted, directed graphs. Acemoglu et al (2012) combine network theory with input-output data to study to what extent idiosyncratic sectoral shocks can affect aggregate business cycle fluctuations.…”
Section: Among Othersmentioning
confidence: 99%
“…An early attempt taking input-output as the starting point can be found in Olsen (1992). More recently McNerney (2009) studies the network properties of input-output models, while Blöchl et al (2011) use centrality measures and clustering techniques to uncover salient structural features of economies based on an interpretation of input-output tables as weighted, directed graphs. Acemoglu et al (2012) combine network theory with input-output data to study to what extent idiosyncratic sectoral shocks can affect aggregate business cycle fluctuations.…”
Section: Among Othersmentioning
confidence: 99%
“…And because 2, 3, 5 are in the same cycle 2 → 5 → 3 and 2 → 4 → 5 → 3, they have the same values of t jj . Next, we compare our first-passage flow distance l ij with shortest path distance and first-passage distance based on random walks [41] on the closed version of the same network. In the latter comparison, "source" and "sink" are excluded so that the network is closed.…”
Section: Calculation On An Example Networkmentioning
confidence: 99%
“…Both the shortest path distance [38], resistance distance [39] and the mean first-passage distance of a random walker [40][41][42][43] can reflect the intrinsic properties of the graph. However, conventional first-passage distance on a graph is based on the basic assumption that the whole network is closed, which means the random walker cannot escape from the network, thus the total number of walkers on the graph is conservative.…”
Section: Introductionmentioning
confidence: 99%
“…F. Cerina et al [12] reported that network-based measures such as community coreness and PageRank centrality are more helpful in identifying key industries than traditional inter-industry analysis methods such as backward linkages. F. Blochl et al pointed out the limitations of traditional centralities and suggested the random walking centrality and the counting betweenness [11]. They reported that the measures are suitable to find the most immediately affected industry and the longest affected industry, respectively.…”
Section: Introductionmentioning
confidence: 99%